Perangkat Lunak Berbasis Opensource di Bidang Telekomunikasi Untuk Menumbuhkan Minat Siswa di Purwakarta terhadap Teknologi - Endah Setyowati; Galura Muhammad Suranegara; Ichwan Nul Ichsan (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2021)
Nowadays, opensource-based technology has begun spreaded into telecommunications field. It can be seen by the number of distributed opensource-based software tools at telecommunications field. The use of opensource based software has a huge impact both on the speed of innovation and for any individual that involved in opensource based projects. The Sistem Telekomunikasi Study Program from Universitas Pendidikan Indonesia Purwakarta Regional Campus has held an opensource introduction activity in the field of telecommunications for high school students (SMA, MA, SMK) in Purwakarta at August 29, 2020. This activity aims to introduce the opensource paradigm to grow their interest and attraction of participants to start looking at source code, trying to use it thus they can contribute to opensource projects. Activities are held offline according to the Covid-19 protocol using blended learning method. The results of the activity showed that the participants were very satisfied with the event and interested in further learning about opensource based tools.